Black muslim women in security studies. Issue 1 (2nd January 2021) - Ahmed Ali, Fatuma; Mwambari, David
ABSTRACT: We are interested in the politics of stigmatised bodies at the intersection of race and gender, seen as threats and/or victims. Using the case study of Kenya, this essay examines how the recent history of the War on Terror and counter-terrorism measures have shaped policy, practice, and scholarship on security to brand Black Muslim Women in Kenya as terrorist suspects. It asks how Black Muslim women are alienated in security studies due to their gender, race, religion, and class.